PEMODELAN PASANG SURUT TERHADAP SURF ZONE MENGGUNAKAN SURFER, FORTRAN C++ DAN GIS PADA PANTAI KOTA MAKASSAR - Riswal Karamma; Ahmad Syarif Sukri (Informatics Engineering Department of Halu Oleo University, 2018)
Surf zone is the most important area in the analysis of the coastal process because in that area three waves are no longer stable due to the energy lost after the wave breaks so that high turbulence occurs which causes the sediment transport process. The purpose of this research was to determine the width of the surf zone during high tide and low tide on the coast of Makassar City starting from the estuary of the Jeneberang River to the estuary of the Tallo River. Data analysis technique used in the form of wind direction and velocity analysis use the application surfer, fortranC++and GIS, effective fetch analysis, wave forecasting, and breaking wave analysis then measured the width of the surf zone using the bathymetry map of the research site. The results of this research are the average width of the surf zone in the research site affected by the tides where the widest average surf zone width occurs at low tide with a width of 618 meters and the narrowest average width of the surf zone occurs when the tide is 35 meters wide.Keywords—Coastal Area, Tides, Wide Surf ZoneDOI : 10.5281/zenodo.1911853